2012
DOI: 10.1080/10810730.2012.712625
|View full text |Cite
|
Sign up to set email alerts
|

What Do Health Literacy and Cultural Competence Have in Common? Calling for a Collaborative Health Professional Pedagogy

Abstract: Limited health literacy is recognized as contributing to racial/ethnic and other health disparities through mechanisms of poor understanding and adherence, and limited access to health care. Recent studies have focused on interventions to address literacy gaps between patients and healthcare providers, focusing on communication techniques and redefining the responsibility for closing gaps. Cultural differences between patient and provider, if left unaddressed, have been shown to contribute to poor health outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 24 publications
0
66
0
Order By: Relevance
“…Areas that should be addressed in health literacy and cultural competence training include involving community stakeholders for training, to help reflect upon the needs of the individuals and families that they treat [34]. Evaluation of the impact of such training could include patient satisfaction with encounters with health professionals.…”
Section: Interpersonal Community and Cultural Influences And Health mentioning
confidence: 99%
“…Areas that should be addressed in health literacy and cultural competence training include involving community stakeholders for training, to help reflect upon the needs of the individuals and families that they treat [34]. Evaluation of the impact of such training could include patient satisfaction with encounters with health professionals.…”
Section: Interpersonal Community and Cultural Influences And Health mentioning
confidence: 99%
“…In the New Zealand context, for example, there is a requirement under the HPCAA to communicate effectively with Māori patients, including simple measures such as proper pronunciation of Māori names, although this is still quite challenging for some practitioners (Bacal, Jansen, & Smith, 2006). Lie, Carter-Pokras, Braun, and Coleman (2012) have identified that both health literacy and cultural differences between patients and providers can contribute to health disparities, and that these gaps are likely to expand with increasingly ethnically diverse and older populations. They argue that these two fields are both inherently difficult to address and tend to be taught separately in health professional education programs.…”
Section: Discussionmentioning
confidence: 99%
“…They argue that these two fields are both inherently difficult to address and tend to be taught separately in health professional education programs. For this reason, they have proposed an educational model for addressing health literacy and cultural differences concurrently (Lie et al, 2012). We believe that this framework could be adopted for use in educational programs in New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…Although cultural competency education and training has been recommended to partially address these concerns, little research has been conducted on the impact of such training on health outcomes. 20 Related questions include 21 : what are the best practices, effective teaching methods, and faculty development in health literacy and cultural competency training? Can communication training focused on underserved populations change behavior and enhance patient comprehension?…”
Section: Current State Of Research On Racial and Ethnic Disparities Imentioning
confidence: 99%